Development and Control of Hand Exoskeleton System Using Intended Movement - Shahrol, Mohamaddan; Herman, Khamis; Annisa, Jamali; Saidatul Ardeenawatie, Awang; noor ayuni, Che zakaria; Akihiko, Hanafusa (2021)
Hand motor impairment is a common disability among stroke survivors that severely affect their ability in activities of daily livings (ADLs), reducing independence and quality of life. Throughout the rehabilitation process, stroke patients able to regain partially or fully the hand motor function. However, the conventional rehabilitation process is limited by the insufficient number of therapists, labor-intensiveness, and low compliance. The objective of this study was to support the rehabilitation process and ADLs through the development of the Flexible Linkage Hand Exoskeleton Rehabilitation Robot (FLEXOR), a five fingers 3D printed prototype actuated by linear actuators. FLEXOR was controlled using intended movement to support the independent exercises and to assist the ADLs movement. An Arduino-based control system driven by electromyography (EMG) signal was developed for FLEXOR. The new control system protected the hand against over-flexing and excessive application of force. The control system was programmed into three different operating modes which enable FLEXOR to provide passive exercises to the fingers, assist fingers in ADLs movement with minimal efforts, and provide active exercises while assisting fingers in ADLs.